Metode Montessori Berbantu Alat Peraga Matematika Berbahan Limbah Karet Spons untuk Mengembangkan Partisipasi Aktif Siswa SD: Montessori Method Assisted Math Tools Made from Rubber Sponge Waste for Developing Elementary Students Active Participation - Susilawati, Susilawati (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to determine the implementation of Montessori learning methods based on mathematical props made from sponge rubber waste in developing active participation of fifth grade elementary school students. This study uses descriptive qualitative research methods using instruments in form of observation sheets, interview sheets, questionnaire sheets, and documentation. The collected data is analyzed by triangulation. The results showed that Montessori learning based on mathematics teaching aids made from sponge rubber waste can develop active participation of fifth grade students. Active participation of fifth grade students looks better when teachers apply Montessori learning method. This can be seen from the increase in the average value of students' active participation at each meeting. At the first meeting the average value of active student participation was 66.67, the second meeting was 73.91 and the third meeting was 81.52. This study recommends implement the learning methods needed with interesting tools, so that it can increase students’ active participation.